Advances and recent applications in LC-MS and HPLC - Azharuddin, Quazi Syed; Mahajan, Devidas T.; Masand, Vijay H.; Alafeefy, Ahmed M.; Gajbhiye, Jayant M.; El-Sayed, Nahed Nasser Eid; Wajid, Abdul; Mohammad, Noor (Elsevier, 2015)
Advances and Recent Applications in LC-MS and HPLC presents the most recent developments in liquid chromatography and mass spectrometry techniques. The book’s content reaches across a range of disciplines and cites several case studies to effectively capture the advanced applications that make LC-MS and HPLC multifunctional and exacting techniques. Liquid chromatography and mass spectrometry systems generate chromatograms of column peaks and can provide molecular weights of separated materials and their solvent complexes. However, while these systems can provide structural information to confirm the identity of the compounds separated, the process is very expensive. This book provides identification of simple compounds resulting from fragmentation studies and their subsequent results, offering the reader access to information unavailable elsewhere and allowing researchers to avoid incurring the costs associated with obtaining the hands-on results that LC-MS systems generate. Applicable to chemical analysis, bioanalysis, and medicinal chemistry, as well as pharmaceutical science, synthetic chemistry, and industrial chemistry, Advances and Recent Applications in LC-MS and HPLC is a multidisciplinary reference that arms scientists with the latest research. Detailed case studies enable researchers to make the book's concepts immediately implementable.